OPTIMALISASI PEMANFAATAN TERMINAL TAMANSARI DALAM RANGKA PENINGKATAN PELAYANAN TRANSPORTASI PUBLIK DI KOTA SALATIGA - sahal kurniawan; Puji Astuti; Supratiwi . (Journal of Politic and Government Studies, 2013)
AbstractOptimization of utilization of Tamansari station in order to increase public transportationservices in the city of Salatiga is a variety of efforts made in developing governmenttransportation Salatiga city which until now still not running at maximum. The findings showthat the situation of tamansari station doesn't go Past optimally due to many factors such as (1)a terminal Condition is not in accordance with the conditions of Salatiga, (2) the TransportConditions is overload on certain routes, (3) a very good road conditions but are not offset bythe condition of the terminal itself, (4) The number of staff that are minimal, the quality of thedriver as well as a growing community of low leaving city transport as a means of publictransport. Of the issues the City Government has made numerous attempts, such as: Restrictionson the route permit routes already crowded city transport, standardization, standardization oftransport drivers, as well as the total renovation of the terminal doing Tamansari StationSalatiga. In the implementation, optimisation of terminal has not been walking Past it perfectlyand still requires a lot of time, especially after the refurbishment had been completed.Keyword : Optimalization, Station, Transportation, Public